Keragaman Padi Lokal Asal Rokan Hilir Riau Berdasarkan Karakter Agro-Morfologi - Siti Fatonah; Fitmawati Fitmawati; Zutia Wulandari; Erwina Juliantari (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2019)
Local rice was an important source of germplasm for superior rice breeding programs. This study aims to identify the diversity of five local rice accessions from Rokan Hilir regency of Riau based on agro-morphological characters. Identification was carried out using agronomic and morphological characters from samples of rice plants taken on farmers' fields. Data were analyzed using ANOVA (Analysis of variance), similarity matrix, SAHN grouping analysis (Sequential Aglomerattive Hieararchical and Nested Clustering) and Pearson Correlation analysis. The results showed that most quantitative and qualitative characters showed high variation, including ability to reproduce, level of excitement, plant height, stem diameter, 100 seed weight, grain length, stem stiffness, leaf surface, leaf angle, leaf neck color, leaf color, and ligule color. The highest phenotype similarity coefficient was 0.571, there are between Pulut bawang and sekuning accessions, while the lowest phenotype coefficient was 0.238 between Sigudang and IR64 accessions. The cluster analysis results in a dendogram with similarity coefficient of 0.40 to 0.572. All accessions of Rokan Hilir rice were united in the similarity coefficient of 0.40 and five accessions were grouped into two main clusters, namely Cluster I (Sigudang dan Pulut minyak) dan Cluster II (Pulut bawang, Sekuning, IR64). Correlation analysis between agro-morphology traits showed a high correlation such as stem trunk and stem stiffness, stem weight and plant age, plant age and stem stiffness, flag leaf angle and leaf angle, leaf blade color and leaf angle, leaf blade color and flag leaf angle.